Sosialisasi Penggunaan Media Tangga Pintar Satuan Berat Pada SD Negeri Malaka - Yufrizal Yufrizal (Jurnal Kabar Masyarakat, 2023)
This service is motivated by problems found in the field regarding the low level of understanding of students in mastering the concept of measuring units of weight for Class III students at SD Negeri Malacca, namely that some students still do not understand mathematical concepts in the material about units of weight. This happens because teachers are still not precise in choosing media and models in learning, and teachers do not play an active role, therefore it is seen that students lack enthusiasm in learning. Teachers must choose media and models that are interesting, creative and innovative. Therefore, teachers take steps using Smart Unit Ladder Media to improve students' understanding in mathematics learning. The approach or method used is Participatory Action Research (PAR) which is a research approach that involves active participation from community groups who are research subjects. This method aims to produce knowledge that is relevant, useful and can be applied in everyday life. This activity was carried out at Malaka State Elementary School Class III. With the existence of smart ladder media with weight units, students will be motivated and happier and will increase or improve their learning outcomes by using the media.